Learning Space in Public Secondary Schools for Students Psychological Development and Well Being - Sabrina Ismail, Alice; Abdullah, Sufrie (International Journal of Engineering and Technology, 2018)
This paper explores on learning spaces in Malaysiaâ€™s public secondary school as it plays vital role that responds towards studentsâ€™ psychological needs. Past literature on public secondary schools in Malaysia only focuses on teaching and learning methods as well as from the aspect of school management and maintenance. None of the above literature discusses on how to design appropriate learning space in Malaysian public secondary schools. To conduct this study, qualitative and quantitative methods involving perception of public secondary school students and direct observation on two selected case studies were done to establish appropriate learning space design attributes. There are two key factors that contributed in the psychological development of student in their learning environment. These are the physical classroom aspects like access and circulation, classroom proportion, furniture layout, and technology capability. as well as the the functional characteristics of learning space involving the air quality, room temperature, Â lighthing dan acoustics. Â The findings are of benefits for future designers, builders, education providers and related authority to build conducive learning space to improve the quality of public education infrastructure for students learning advancement in the future.Â